Conformational changes of DNA induced by a trans-azobenzene derivative via non-covalent interactions. Issue 35 (22nd August 2018) - Zhang, Hong; Fu, Haohao; Shao, Xueguang; Chipot, Christophe; Monari, Antonio; Dehez, François; Cai, Wensheng
Abstract : The presence of only one interacting azobenzene is not sufficient to lead to a global conformational change from B- to A-DNA. Abstract : In biological environments and in aqueous solution, DNA generally adopts the canonical B conformation. Recently, an azobenzene photoswitch containing a polyamine chain with three positive charges was shown to induce a reversible conformational transition between the A and B forms of DNA, the transition being triggered by trans – cis isomerization of the photoswitch upon non-covalent intercalation. It was proposed that, in its trans conformation, azobenzene stabilizes the A form of DNA. The structural details and the mechanism upon which trans -azobenzene induces the B-to-A DNA transition remain, however, unclear. In the present work, two possible intercalating modes of trans -azobenzene, from the minor groove and from the major groove, were investigated with all-atom molecular-dynamics simulations. Intercalation from the major groove was found to be the most probable binding mode due to favorable electrostatic and π–π stacking interactions. The free-energy profile associated with the B-to-A conformational transition reveals that intercalation from the major groove leads to a conformational change of DNA, showing a slight tendency to interconvert from B- to A-DNA, in agreement with the CD spectrum obtained from the experiment. However, the presence of only one interacting azobenzene is not sufficient to lead to a global conformational change to A-DNA. The present results are expected to serve in the design of DNA switches, which can induce reversible DNA conformational changes.